Stunting is influenced by toddler and maternal characteristics, history of infectious disease, IYCF practices, and protein intake: case control study in Nabire coastal areas, Indonesia - Ibrahim, Nur Indah Fitriana; Khomsan, Ali; Riyadi, Hadi (International Journal Of Community Medicine And Public Health, 2023)
Background: Stunting is one of the unresolved nutritional problems in Indonesia. The coastal areas of Nabire Regency have a high prevalence of stunting, which is more than 20%. This study aims to further analyze the risk factors for stunting in children aged 6-24 months in the coastal area of Nabire Regency. Methods: The research design used was a case-control study with matching age, gender, socioeconomics, and village monographs, performed in August 2022-June 2023. The number of samples in this study was 112 subjects (children’s 6-24 months). Collected by questionnaires, data of family characteristics, toddler characteristics, maternal characteristics, history of infectious diseases, IYCF practices, nutritional intake of toddlers, complete basic immunization status of toddlers, maternal anemia history, maternal SEZ history, and maternal ANC history. The risk of independent variables was analyzed by logistic regression test by SPSS 16. Results: The results showed that the risk factors for stunting were birth length (OR=6.38), birth weight (OR=6.73), current weight (OR: 15.59), history of anemia during pregnancy (OR=19.60), history of ANC during pregnancy (OR=41.88), frequency of respiratory infection (OR=39.00), frequency of diarrhea (OR=2.37), early initiation of breastfeeding (OR=0.33), exclusive breastfeeding (OR=0.41), 6-24 months breastfeeding (OR=0.39), complementary feeding practices (OR=2.60), protein intake (OR=6.75). Conclusions: Nabire Regency with its diversity of socio-cultural life, and unique geographical conditions, certainly has problems and determinants of stunting that are different from other parts of Indonesia. The most influential risk factor for stunting is the history of ANC during pregnancy and frequency of respiratory infections.